Excavations at Kaimes Hill, Ratho, City of Edinburgh, 1964 -72 (Proceedings of the Society of Antiquaries of Scotland, 2005)
Kaimes Hill, City of Edinburgh, has been the focus for both antiquarian and modern archaeological research since at least the mid-nineteenth century and has produced evidence for activity dating from the Mesolithic through to the medieval period. The paper assimilates this evidence, provides a complete account of the excavations undertaken over the ramparts, `hut circles', prehistoric ritual and funerary monuments by D D A Simpson between 1964--72, and presents the results obtained from recent artefactual analysis and radiocarbon dating. Specialist reports include